Assessing Biosynthetic Gene Cluster Diversity of Specialized Metabolites in the Conserved Gut Symbionts of Herbivorous Turtle Ants - Chanson, Anaïs; Moreau, Corrie S.; Duplais, Christophe (Frontiers in Microbiology, 2021)
Cephalotes are herbivorous ants (>115 species) feeding on low-nitrogen food sources and they rely on gut symbionts to supplement their diet by recycling nitrogen food waste into amino acids. These conserved gut symbionts, which encompass five bacterial orders, have been studied previously for their primary nitrogen metabolism, however little is known about their ability to biosynthesize specialized metabolites which can play a role in bacterial interactions between communities living in close proximity in the gut. To evaluate the biosynthetic potential of their gut symbionts we mine 14 cultured isolate genomes and gut metagenomes across 17 Cephalotes species to explore the biodiversity of biosynthetic gene clusters (BGCs) producing specialized metabolites. The diversity of BGCs across Cephalotes phylogeny was analysed using sequence similarity networking and BGC phylogenetic reconstruction. Our results reveal that the conserved gut symbionts involved in the nutritional symbiosis possess 80% of all the 233 BGCs retrieved in this work. Furthermore the phylogenetic analysis of BGCs reveals different patterns of distribution suggesting different mechanisms of conservation. A siderophore BGC shows high similarity in a single symbiont across different ant host species whereas a BGC encoding the production of non-ribosomal peptides (NRP) is found is different symbionts within a single host species. Additionally, BGCs were abundant in four of the five bacterial orders of conserved symbionts co-occurring in the hindgut. However one major symbiont localized alone in the midgut lack BGCs. Because the spatial isolation prevents direct interaction with other symbionts this result supports the idea that BGCs are maintained in bacteria living in close proximity but are dispensable for an alone-living symbiont. These findings together pave the way for studying the mechanisms of BGCs conservation and evolution in gut bacteria genomes associated with Cephalotes. This work also provides a genetic background for further study aiming to characterize bacterial specialized metabolites and to understand their functional role in multipartite mutualisms between conserved gut symbionts and Cephalotes turtle ants.